2017
DOI: 10.14233/ajchem.2017.20755
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Biomimetic Hydroxy Apatite-Silver Impregnated Soy Protein Isolate Nanocomposites for Dental Implantations

Abstract: A novel class of biomimetic hydroxyapatite (HAP), poly(vinyl alcohol) (PVA) and silver nanoparticles (AgNPs) impregnated soy protein isolate (SPI)-ternary and quaternary nanocomposites were fabricated by an environmentally benign hydrothermal precipitation process under UV irradiation. Various physico-chemical and mechanical characteristics showed improved mechanical properties that open up newer vistas in biomedical applications, especially for dental implantations and repairs. The SEM, FT-IR, powder-XRD, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The differentiation between chemical processes is represented by the reduction agents and stabilizers used, such as sodium citrate, ascorbate, sodium borohydride (NaBH 4 ), elemental hydrogen, polyol process, Tollens reagent, n , n -dimethylformamide (DMF), and poly (ethylene glycol)-block copolymers. Several protective agents (stabilizers) have been used, such as thiols, amines, acids, alcohols [ 93 ], and polymeric compounds such as chitosan [ 25 , 26 , 56 ] and polymethylmethacrylate [ 27 , 51 , 53 , 68 , 92 ]. These agents stabilize dispersive NPs during their synthesis and protect NPs that can be absorbed on, or bind onto, nanoparticle surfaces, avoiding their agglomeration and sedimentation [ 94 ].…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The differentiation between chemical processes is represented by the reduction agents and stabilizers used, such as sodium citrate, ascorbate, sodium borohydride (NaBH 4 ), elemental hydrogen, polyol process, Tollens reagent, n , n -dimethylformamide (DMF), and poly (ethylene glycol)-block copolymers. Several protective agents (stabilizers) have been used, such as thiols, amines, acids, alcohols [ 93 ], and polymeric compounds such as chitosan [ 25 , 26 , 56 ] and polymethylmethacrylate [ 27 , 51 , 53 , 68 , 92 ]. These agents stabilize dispersive NPs during their synthesis and protect NPs that can be absorbed on, or bind onto, nanoparticle surfaces, avoiding their agglomeration and sedimentation [ 94 ].…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Studies have also revealed that AgNP exerts antibacterial activity against Streptococcus mutans [ 3 , 42 , 49 , 60 , 69 ], Staphylococcus aureus [ 3 , 54 , 58 , 69 , 74 , 93 ], Streptococcus sobrinus , Lactobacillus acidophilus , Lactobacillus casei [ 42 ], Streptococcus sanguinis [ 49 ], Enterococcus faecalis [ 69 , 93 ], and Actinomyces actinomycetemcomitans [ 49 ]. AgNPs also prevent the formation of E. faecalis , S. aureus , Streptococcus gordonii , Streptococcus mitis , and Streptococcus mutans biofilms [ 30 ].…”
Section: Silver Nanoparticles and Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, silver nanoparticles were synthesized into SPI/HAP/PVA composites by a green method using UV radiation. The synthesized nanocomposites exhibited enhanced antibacterial activity against five different bacterial strains; the authors claimed that it could be a potential candidate for orthodontic applications [140]. Qu et al demonstrated that incorporating highly dispersible TiO 2 nanoparticles is an effective approach for enhancing the mechanical, thermal, and antimicrobial properties of zein/chitosan films.…”
Section: Plant Proteinsmentioning
confidence: 99%
“…[ 31 ] Therefore, various nanofillers are introduced into SPI/PVA materials. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%